Dampak Target Konsumsi Listrik Nasional Terhadap Perekonomian di Provinsi Papua: Pendekatan Analisis Tabel Input-Output - Taridipa, Fitrisia; Shabrina, Amara Putri; Setiawan, Kevin Rizkika; Kartiasih, Fitri (PPJP ULM, 2024)
The study focuses on Papua Province, which has the lowest electrification rate in Indonesia. It aims to analyze the potential of the electricity and gas procurement sector in 2022 and the impact of economic acceleration policies through increased per capita electricity consumption. The data used are from the 2016 Papua input-output table by BPS Statistics Indonesia, updated using the RAS method. The analysis shows that the electricity and gas procurement sector plays a crucial role in sustainable economic growth, significantly contributing to economic output, and showing high sensitivity to changes in other sectors. Simulations of increased per capita electricity consumption indicate substantial output growth in the electricity and gas sector, as well as positive impacts on other sectors. Therefore, investments and policies supporting electricity infrastructure development are essential to maximize Papua's economic potential and improve welfare. This study guides policymakers and stakeholders in designing sustainable development strategies for Papua Province.